Menanamkan Nilai Kewirausahaan Melalui Kegiatan Market Day Kecil-Kecil Jadi Wirausahawan - Rahayu, Yayuk Desti (CV. Supernova Office Stationary and Printing, 2023)
Entrepreneurship is an attitude of mental and spirit which is always active and creative, down to earth, and striving in order to increase profit for business activities. There are six basic values of entrepreneurship which can be integrated in early childhood learning process, namely: independent, creative, risk taker, leadership, action orientation, and hard work. The embedding of entrepreneur’s character was one of the ways in realizing the vision of Permata Bangsa Kindergarten by making the program “Kecil-kecil jadi Wirausahawan”. The activity was not only focused on the market day (sale) activity, but the children were taught to produce, to package and also to market product. The research method used qualitative research with case study method. This study aimed to investigate the actual conditions about the embedding of entrepreneurial values through market day activity for early childhood at the Permata Bangsa Kindergarten.The results of market day activity can be used as one way to embed the entrepreneurship values early on. So, they will no longer become job seekers but they will open jobs after graduating from school.